Tabayyun in the Digital Marketplace: Quranic Ethics Against Skincare Overclaims - Yanuar, Mutiara; Abdul Karim (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
In the digital era, overclaims in product advertisements, especially in the skincare sector, on e-commerce platforms have become increasingly widespread and challenging for consumers to verify. This study aims to examine the relevance of QS. Al-Hujurat [49]:6 through the lens of tafsir in addressing the ethical implications of misleading promotional content. Using a qualitative descriptive method, this research integrates thematic tafsir analysis with contemporary case studies of skincare product marketing on Shopee. The findings show that the Qur’anic principle of tabayyun (verification) remains highly relevant as a moral compass for both consumers and sellers in navigating the flood of information and commercial persuasion. Tafsir scholars emphasize the urgency of critical information filtering before passing judgment or making decisions, especially in spaces vulnerable to manipulation and disinformation. The study concludes that implementing tabayyun values can serve as a foundation for ethical consumerism and digital literacy. It is recommended that Qur’anic principles be more actively integrated into media and advertising ethics to establish a marketplace founded on honesty, trust, and responsibility.